Characterizing Early Childhood Disabilities in a Nationally Representative Sample Using Functional Profiles. (July 2015) - McLaughlin, Tara W.; Snyder, Patricia A.; Algina, James
The present study combined a functional abilities approach to characterizing childhood disability with person-oriented analytic techniques to identify and describe functional profiles of young children with disabilities. Nationally representative data from the Pre-Elementary Education Longitudinal Study was used, which included nearly 3, 000 preschool children with disabilities. Exploratory analyses using latent class analysis were conducted to determine if distinct and interpretable subgroups of children based on shared profiles of functional ability would emerge. Five distinct latent subgroups were identified, and functional profiles for these subgroups are described. The authors examined classification accuracy and describe demographic characteristics, activity participation levels, and environmental conditions for each subgroup. The utility of a functional approach to examining childhood disability in special education and related fields is discussed.